Imag(in)ing the war in Japan : representing and responding to trauma in postwar literature and film - Stahl, David C., 1959-; Williams, Mark, 1957- (Brill, 2010)
This study of a series of artistic representations of the Asia Pacific War experience in a variety of Japanese media is premised on Walter Davis' assertion that traumatic events and experiences must be 'constituted' before they can be assimilated, integrated and understood. Arguing that the contribution of the arts to the constitution, integration and comprehension of traumatic historical events has yet to be sufficiently acknowledged or articulated, the contributors to this volume examine how various Japanese authors and other artists have drawn upon their imaginative powers to create affect-
Keywords: Japanese literature -- 20th century -- History and criticism.; World War, 1939-1945 -- Japan -- Literature and the war.; Motion pictures -- Japan -- History -- 20th century.; World War, 1939-1945 -- Japan -- Motion pictures and the war.; Psychic trauma in literature.; Psychic trauma in motion pictures.; Littérature japonaise -- 20e siècle -- Histoire et critique.; Guerre mondiale, 1939-1945 -- Japon -- Littérature et guerre.; Cinéma -- Japon -- Histoire -- 20e siècle.; Guerre mondiale, 1939-1945 -- Japon -- Cinéma et guerre.; Traumatisme psychique dans la littérature.; Traumatisme psychique au cinéma.; LITERARY CRITICISM -- Asian -- General.; Japanese literature; Motion pictures; Psychic trauma in literature; Psychic trauma in motion pictures; War and literature; War and motion pictures; Japan; Literatur; Zweiter Weltkrieg -- Motiv; Film; Literatur.; Japanisch.; Nachkriegszeit.; Psychisches Trauma.; 1900-1999; Criticism, interpretation, etc.; History